2022
DOI: 10.1093/braincomms/fcac289
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards a taxonomy of cognitive impairments in epilepsy: application of latent profile analysis to 1178 patients with temporal lobe epilepsy

Abstract: In efforts to understand the cognitive heterogeneity within and across epilepsy syndromes, cognitive phenotyping has been proposed as a new taxonomy aimed at developing a harmonized approach to cognitive classification in epilepsy. Data- and clinically-driven approaches have been previously used with variability in the phenotypes derived across studies. In our study, we utilize latent profile analysis to test several models of phenotypes in a large multicenter sample of patients with temporal lobe epilepsy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The overall impairment classification rate for the MoCA domains (40%) was somewhat similar to the IC‐CoDE (34%), providing some evidence that the domains in the MoCA are sensitive to broader cognitive impairments beyond memory. The ability of the MoCA to detect non‐amnestic cognitive changes increases its clinical utility in epilepsy, as the cognitive profiles observed are broader compared to many other neurological conditions 14,22,38,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…The overall impairment classification rate for the MoCA domains (40%) was somewhat similar to the IC‐CoDE (34%), providing some evidence that the domains in the MoCA are sensitive to broader cognitive impairments beyond memory. The ability of the MoCA to detect non‐amnestic cognitive changes increases its clinical utility in epilepsy, as the cognitive profiles observed are broader compared to many other neurological conditions 14,22,38,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…In the study by Reyes et al, 4 7 epilepsy centers pooled their neuropsychological data to try to tackle this question. They use an analytical technique termed latent profile analysis (LPA) 5 which belongs to the family of person-centered statistical approaches and provides advantages over the techniques used to date; cluster analysis and using prespecified cutoffs for impairment (such as having scores 1 or 1.5 standard deviations below the mean).…”
Section: Commentarymentioning
confidence: 99%
“…Our group has shown that in young-to-middle aged adults, the phenotyping approach better captures the heterogeneity inherent both within and across epilepsy syndromes compared to analyzing individual scores in isolation (40, [49][50][51][52][53][54][55]. We have demonstrated that cognitive phenotypes are stable and robust across cohorts and are associated with distinct patterns of brain imaging abnormalities (49,51,56,57).…”
Section: Introductionmentioning
confidence: 99%